Evaluation of new chromogenic substrates for the detection of coliforms - Browne, Nicola; Huang, Z.; Dockrell, M.; Hashmi, P.; Price, R. (Blackwell Science Ltd, 2010)
Aims: To evaluate a new range of chromogenic substrates for the detection of ß-galactosidase activity in coliforms and to compare their performance in agar media and broths.Methods and Results: Sixteen novel galactoside substrates were prepared and incorporated into agar and broth. Their performance was compared using Escherichia coli (five strains), Salmonella (two strains), Enterobacter (two strains), Klebsiella, Pseudomonas, Listeria, Serratia, Shigella, Citrobacter, Proteus and Staphylococcus as well as pathological urine samples. The six substrates out of the initial 16 that showed the greatest sensitivity were VQE-gal, VQM-gal, VLPr-gal, VLE-gal, VLM-gal and VBzTM-gal, whose released chromophores were red, brown or purple. VQE-gal and VLPr-gal were studied in greater detail and were incorporated into agar medium. Coliform colonies appeared red and brown respectively, following incubation at 37°C for 24 h; however, positive results were obtained within a working day. The VQE-gal medium was compared with some commercially available media.Conclusions: The range of substrates described can be used in broths as well as in agars. The VQE agar allows the detection of coliforms within a working day. VQE-gal medium proved to be more sensitive when compared to other available chromogenic media and allows the unambiguous detection of coliforms.